Contribuição à técnica de dissecação em Harpacticoidea (Copepoda, Crustacea) - Jakobi, Hans; Fonseca, Veronica Gomes da (Acta Biológica Paranaense, 1981)
Contribuição à técnica de dissecação em Harpacticoidea (Copepoda, Crustacea)